1986
DOI: 10.3109/00016488609132845
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Maxillary Sinusitis:Definition, Diagnosis and Relation to Dental Infections and Nasal Polyposis

Abstract: Various definitions have been proposed for the term 'chronic sinusitis' but too often reports on chronic sinusitis lack a definition. In order to improve the diagnosis and treatment of this disease, and also to facilitate comparisons between clinical investigations, definitions of 'chronic maxillary sinusitis' of either rhinogenous or dental origin are proposed. It is suggested that the differential diagnosis should be based upon the duration of symptoms, ENT and dental examinations, sinus radiographs and/or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(105 citation statements)
references
References 9 publications
5
98
0
Order By: Relevance
“…Recently, guidelines have advocated division of CRS into NP and no NP. In the same study, Melen et al 7 noted NP were associated with OMS in 13.1% of cases and 23.4% of non-OMS cases. Similarly, bilateral sinus disease was less frequent in OMS cases than in non-OMS cases, 18% and 23%, respectively.…”
Section: Sinusitis Guidelines That Reference Omsmentioning
confidence: 88%
See 2 more Smart Citations
“…Recently, guidelines have advocated division of CRS into NP and no NP. In the same study, Melen et al 7 noted NP were associated with OMS in 13.1% of cases and 23.4% of non-OMS cases. Similarly, bilateral sinus disease was less frequent in OMS cases than in non-OMS cases, 18% and 23%, respectively.…”
Section: Sinusitis Guidelines That Reference Omsmentioning
confidence: 88%
“…Careful examination of these source documents shows that they fail to support this incidence. In a more recent investigation of the incidence of OMS, Melen et al 7 found that in a highly selected population of 198 adults referred for evaluation with refractory CRS, 40% of affected maxillary sinuses were from an odontogenic cause and of these 18% were bilateral OMS. Recently, guidelines have advocated division of CRS into NP and no NP.…”
Section: Sinusitis Guidelines That Reference Omsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral bacteria may ascend from the mouth through the middle meatus to the maxillary sinus, or through the Eustachian tube to the middle ear, causing infections. Dental conditions such as periodontitis or periapical granuloma have been associated with 40 % of chronic maxillary sinusitis cases (Melen et al, 1986). Typically oral anaerobic bacteria such as Porphyromonas, Prevotella and Fusobacterium species can be detected by culture methods in infections of the middle ear (Brook et al, 2000), tonsils (Rajasuo et al, 1996) and sinuses (Le Moal et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the finding is discovered by chance through routine radiographic examinations. Symptomatic cases may occur when the sinus is completely full, the most common clinical manifestations being that of headaches, periorbital and hemifacial pains, and sometimes dizziness, nasal obstruction and recurrent sinusitis, among others (2,3). The incorporation of tomographic tests performed in order to assess implant treatment has led to an increase in the diagnosis of these types of disorders, which occasionally have an apparent dental origin.…”
Section: Introductionmentioning
confidence: 99%